Tanggung Jawab Pemilik Hewan Peliharaan Atas Kerugian Yang Ditimbulkan Kajian Hukum Perdata - Sahusilawane, Clarion; Saija, Ronald; Pariela, Marselo Valentino Giovani (Faculty of Law Universitas Pattimura, 2025)
The main objective of this research is to investigate the form of liability of animal owners for damage to residents' farms, as well as to reveal strategies for resolving the disputes faced. The research method is normative research, then using data collection techniques using original data, primary, secondary, and tertiary materials. In the discussion of this thesis, the author obtains material on the liability of pet owners for losses caused by civil law studies can be obtained in the Civil Code, consumer protection law. While civil rules, civil law responsibility, and administrative rules. Based on the description above, the author draws several conclusions where protection for consumers is found in the Civil Code, Consumer Protection Law, and Health Law. Furthermore, the liability of pet owners for losses caused by civil law studies can be based on civil law and administrative law.